Development of Ag-ZnO/AgO Nanocomposites Effectives for Leishmania braziliensis Treatment - Rafaela Miranda Barbosa; Malu Mateus Santos Obata; José Rodrigues do Carmo Neto; Rhanoica Oliveira Guerra; Anna Victória Bernardes e Borges; Rafael Obata Trevisan; Letícia Cirelli Ruiz; Júlia de Moura Bernardi; Ana Carolina de Morais Oliveira-Scussel; Sarah Cristina Sato Vaz Tanaka; Fernanda Bernadelli de Vito; Fernanda Rodrigues Helmo; et al. (MDPI AG, 2022)
Tegumentary leishmaniasis (TL) is caused by parasites of the genus Leishmania. Leishmania braziliensis (L.b) is one of the most clinically relevant pathogens that affects the skin and mucosa, causing single or multiple disfiguring and life-threatening injuries. Even so, the few treatment options for patients have significant toxicity, high dropout rates, high cost, and the emergence of resistant strains, which implies the need for studies to promote new and better treatments to combat the disease. Zinc oxide nanocrystals are microbicidal and immunomodulatory agents. Here, we develop new Ag-ZnO/xAgO nanocomposites (NCPs) with three different percentages of silver oxide (AgO) nanocrystals (x = 49%, 65%, and 68%) that could act as an option for tegumentary leishmaniasis treatment. Our findings showed that 65% and 68% of AgO inhibit the extra and intracellular replication of L.b. and present a high selectivity index. Ag-ZnO/65%AgO NCPs modulate activation, expression of surface receptors, and cytokine production by human peripheral blood mononuclear cells toward a proinflammatory phenotype. These results point to new Ag-ZnO/AgO nanocomposites as a promising option for L. braziliensis treatment.